Tingkat Pengetahuan Tentang Kebersihan Gigi Dan Mulut Siswa Sekolah Dasar - Jeanne D'arc Zafera Adam; Jeineke Ellen Ratuela (Indonesian Journal of Public Health and Community Medicine, 2022)
Background: Elementary school students were the one of the population at risk of having health problems, especially dental health. Based on the 2018 Basic Health Research data, the prevalence of dental caries in elementary school students reached 92.6%. One of the determinants of dental and oral health is students' knowledge about dental and oral hygiene. The purpose of this study was to describe the level of students' knowledge about dental and oral hygiene. Methods: This research is a descriptive research. This research was conducted in the city of Tomohon in February-March 2022. This study used 70 respondents. The research variable is knowledge. The research instrument is a questionnaire. The data obtained were analyzed univariately. Results: The results of this study showed that the majority of respondents are female. In addition, it was found that most of the respondents were aged 10-11 years. The results of the measurement of knowledge obtained that the dominant level of knowledge is in the moderate category. Conclusion: It can be concluded that the knowledge of elementary school students about dental and oral hygiene is mostly in the moderate category. Therefore, it is necessary to continue to make efforts to supervise both parents and teachers so that students can practice the knowledge they have so that they can put it into practice.